The 5Q approach - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Reducing hunger and poverty requires effective strategies but many traditional monitoring and evaluation methods are costly, complicated, rigid, slow, and do not include the opinions of the project beneficiaries. The 5Q approach is simple, adaptable, responsive, effective, and better integrates stakeholders. Project beneficiaries can proactively participate in programs for greater livelihood, health, and environmental gains. Developed in cooperation with CIAT. The 5Q approach aims to simplify monitoring, evaluation, and learning (MEL) methods, in order to improve transparency, mutual accountability, and the effectiveness of research and development projects. The fast, easy-to-use, and cost-effective approach offers something that traditional MEL methods don’t: project implementers receive quick feedback on their project in order to make adjustments during the project cycle. Project beneficiaries can proactively participate in programs that directly impact their lives, including throughout the project design, implementation, and evaluation processes, in order to have their needs better understood and met. The 5Q approach asks just 5 simple questions at regular intervals to each one of a project’s stakeholder groups (e.g., farmers, project implementers, and donors) and rapidly analyzes their answers to assess if the project is on track, and if not, adapt quickly. Answers are collected through a means best suited to each group, such as face-to-face surveys, mobile phone apps, web apps, and participatory video. Responses are automatically stored in a central database, processed, and disseminated through an online dashboard to visualize changes – for example in knowledge, attitude, skills, and practices – throughout the project cycle.